2017
DOI: 10.1016/s2214-109x(17)30369-8
|View full text |Cite|
|
Sign up to set email alerts
|

Association between male circumcision and women's biomedical health outcomes: a systematic review

Abstract: SummaryBackgroundMale circumcision reduces men’s risk of acquiring HIV and some sexually transmitted infections from heterosexual exposure, and is essential for HIV prevention in sub-Saharan Africa. Studies have also investigated associations between male circumcision and risk of acquisition of HIV and sexually transmitted infections in women. We aimed to review all evidence on associations between male circumcision and women’s health outcomes to benefit women’s health programmes.MethodsIn this systematic revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
1
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 67 publications
2
66
1
3
Order By: Relevance
“…The present systematic review has contrasted evidence used to argue against MC with evidence from RCTs, systematic reviews, and metaanalyses, in particular, that has demonstrated the multiple medical and health benefits and low risk of MC to males 269,316,427 and their female sexual partners. 249,303 The key publications forming the framework of the present systematic review are provided in Table 10, as required by PRISMA guidelines. We find that, based on the evidence rated by quality, MC, especially when performed in early infancy, is favored.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The present systematic review has contrasted evidence used to argue against MC with evidence from RCTs, systematic reviews, and metaanalyses, in particular, that has demonstrated the multiple medical and health benefits and low risk of MC to males 269,316,427 and their female sexual partners. 249,303 The key publications forming the framework of the present systematic review are provided in Table 10, as required by PRISMA guidelines. We find that, based on the evidence rated by quality, MC, especially when performed in early infancy, is favored.…”
Section: Discussionmentioning
confidence: 99%
“…HIV prevalence was 78% lower ( P = .035) in South African women who only had circumcised male partners . Recent systematic reviews have documented all MC and HIV studies in women …”
Section: Physical Harmmentioning
confidence: 99%
See 2 more Smart Citations
“…Another RCT found that male circumcision decreased Trichomonas vaginalis infection among men (OR 0.49, p = 0.030, AOR 0.41, p = 0.030 (11) among men aged 18-24 years, in Orange farm in South Africa. A systematic review of 57 observational studies also found that females were at a decreased risk of STIs when their male partners were medically circumcised (12). Another systematic review and meta-analysis of global data from April 2019 of 62 observational studies including 119248 men who have sex with men (MSM) found that circumcision was associated with 23% reduced odds of HIV infection among MSM (OR 0.77, 955 CI 0.67-0.89) (13).…”
Section: Introductionmentioning
confidence: 99%